An Introduction to the Scottish Longitudinal Study (SLS) - Williamson, Lee (International Journal of Population Data Science, 2025)
Objective The Scottish Longitudinal Study (SLS) is a largescale research ready record-linkage study created and supported by the SLS Development and Support Unit (SLS-DSU). It links Census through time 1991-2022 to administrative data on major life events, maps changing residential location and for children, their progress through the educational system. Methods This paper will introduce the SLS as a data resource for researchers, the datasets held as part of it, along with the application process for using it. Census data are the building blocks of the SLS from 1991 onwards, for a 5% representative sample of the Scottish population (about 270,000 sample members each Census). The SLS links together a wealth of information from routinely collected administrative data, including vital events registrations (births, deaths and marriages), migration data, Scottish education data, and with appropriate additional permissions can be linked to NHS health data including cancer registry and hospital admission data. Results The size and scope of the SLS make it an unparalleled research resource in Scotland for analysing a range of socio‐economic, demographic and health questions. Additionally, the longitudinal nature of the SLS is particularly valuable, allowing an exploration of causality in a way that cross‐sectional data collected at a single point in time does not. In this way, the SLS can provide insights into the health and social status of the Scottish population and, crucially, how it changes over time. The Scottish Census was a year behind the rest of the UK, with the 2022 Scottish Census data to be linked by SLS summer 2025. The 2025 ADR Conference is an excellent opportunity to showcase the 2022 Census data linkage results. Conclusions The paper will report on preliminary 2022 Census linkage results and SLS-DSU plans to extend research user access arrangements outside of Scotland. As part of the wider UK Census Longitudinal Studies (UKcenLS), the SLS aligns with the ONS-LS for England and Wales and the Northern Ireland LS, facilitating cross-UK analysis.